0322 sleep disordered breathing and MRI makers of brain aging in the Hispanic Community Health Study/Study of Latinos. (25th May 2022) - Ramos, Alberto; Gonzalez, Kevin; Tarraf, Wassim; Redline, Susan; Patel, Sanjay; Stickel, Ariana; Agudelo, Christian; Kaur, Sonya; Testai, Fernando; Lipton, Richard; Isasi, Carmen; Sotres-Alvarez, Daniela; et al.
Abstract: Introduction: We aim to determine if white matter hyperintensities and decreased brain volumes are associated with sleep-disordered breathing (SDB), in a diverse sample of middle-aged and older Hispanic/Latino adults. Methods: Our sample of 1, 119 Hispanics/Latinos (ages older than 50-years; 70% female) from the Hispanic Community Health Study/Study of Latinos (HCHS/SOL) underwent brain magnetic resonance imaging (MRI) as part of the Study of Latinos - Investigation of Neurocognitive Aging MRI (SOL-INCA MRI) ancillary study. MRI outcomes of interest included global (gray matter, total brain) and regional (lobar cortices, hippocampus) brain volumes, lateral ventricle volume, and total white matter hyperintensity (WMH) volume. All MRI measures were residualized for total cranial volume. Our main exposure was visit-1 sleep data (2008-2011), which includes information about SDB defined with the respiratory event index 3% (REI), ≥5 and ≥15 (moderate-severe SDB) identified by home-sleep apnea test. Survey linear regression models to assess the association between sleep measures and MRI outcomes adjusted for age, sex, education, Hispanic/Latino background, body mass index, tobacco use, alcohol consumption, and physical activity factors and accounted for HCHS/SOL complex study design. We tested for effect modifications by age, sex and Hispanic/Latino background. Results: Mean age was 63.9±7.0 years. Adjusting for age, sex, and education, individuals with a REI ≥15 (vs. <5) had decrements in total brain volume (Btotal=-6.115[-10.19 ; -2.04]; p<0.01), total gray matter volume(B= -3.702 [-6.7 ; -0.7]; p<0.05), and frontal cortical gray matter volume (B= -1.844[-3.48; -0.21]; p<0.05), and increments in hippocampal volume β= 0.138[0.04; 0.23]; p<0.01). The associations persisted after adjustment for Hispanic/Latino background and behavioral risk factors. Older age modified associations between the REI and age and total brain volumes (Bage*REI=-0.019[-0.04 ; 0.00]; p<0.05). There was no consistent evidence for effect moderation by sex or Hispanic/Latino background. Conclusion: In a diverse sample of Hispanic/Latinos, moderate-severe SDB was associated with decreased total brain volumes and increments in hippocampal volumes. Our findings suggest that SDB related neuroimaging markers of brain health could serve to identify Hispanic/Latino participants with sleep related Alzheimer's disease and related dementia risk. Support (If Any): This work is supported by National Institute on Aging (R01AG048642, RF1AG054548, and R01AG063868) and by the National Heart Lung Blood Institute (R01HL098297). Dr. González also receives additional support from P30AG59299. The Hispanic Community Health Study/Study of Latinos was carried out as a collaborative study supported by contracts from the National Heart, Lung, and Blood Institute (NHLBI) to the University of North Carolina (N01-philip glass beck HC65233), University of Miami (N01-HC65234), Albert Einstein College of Medicine (N01-HC65235), Northwestern University (N01-HC65236), and San Diego State University (N01-HC65237). The following Institutes/Centers/Offices contribute to the HCHS/SOL through a transfer of funds to the NHLBI: National Institute on Minority Health and Health Disparities, National Institute on Deafness and Other Communication Disorders, National Institute of Dental and Craniofacial Research, National Institute of Diabetes and Digestive and Kidney Diseases, National Institute of Neurological Disorders and Stroke, NIH Institution-Office of Dietary Supplements.